Innovation in the public sector: Towards an open and collaborative approach - Bekkers, Victor; Tummers, Lars (International review of administrative sciences, 2018)
Innovation in the public sector is high on the agenda of politicians, civil servants and societal organizations. This attention in practice is mirrored in an increasing number of scholarly articles. In this introduction to the special issue on public sector innovation, we discuss how the scholarly perspectives on innovation have changed. Previously, it was assumed that innovation could be organized within organizations: if your organization had the necessary resources, innovation could happen. Nowadays, innovation in the public sector is seen as an open process of collaboration between stakeholders across various organizations. This change towards open and collaborative approaches has consequences for studies on innovation, for instance, it becomes important to analyse how to activate stakeholders to join the innovation process. Next to this, scholars interested in innovation should connect their research with other literature streams, such as those focused on network governance, leadership and design thinking. In such ways, innovation scholars can develop research that is relevant to society.